ATR-FTIR detection of secondary structural stability of hemoglobin in hemolysate samples stored at freezing temperature - Htet Htet , Htin Khine; Proungvitaya, Siriporn; Tippayawat, Patcharaporn; Chonanan, Chirapond; Wongwattanakul, Molin (Archives of Allied Health Sciences, 2025)
As for the importance of HbA1c for the diagnosis and monitoring of diabetes patients, many research studies evaluate HbA1c concentration upon storage. However, there are limited studies concerning the structural compositions during storage. The objective of this study was to examine the stability of secondary structure of hemoglobin in hemolysate samples stored for four months using the attenuated total reflectance-fourier transform infrared (ATR-FTIR) spectrometer. The leftover EDTA samples with known HbA1c values were separated into normal and diabetes groups, prepared in hemolysate form, and stored at -20°C. To evaluate the secondary structure of hemoglobin, FTIR spectra were collected for four months using the Agilent 4500 portable FTIR spectrometer (Agilent Technologies, CA). Qualitative and quantitative comparisons of amide I bands were performed in Spectragryph software and Origin software. The difference between the relative intensity ratios of amide A/B and amide I/II were not significant (p-value > 0.05). In qualitative comparison, the position, pattern, and signal intensity of the second derivative spectra remained identical up to four months. In quantitative comparison graph, alpha helix and beta sheet compositions did not show increasing or decreasing trend. This study demonstrated that the structural firmness of hemoglobin in samples remains unchanged after four months of storage at -20°C.